Semblance of Prof. Dr. Raúl Praderi September 18, 1927 - August 1, 2014 Master of surgeons and men’s leader - Pomi, Jorge; Bogliaccini, Gustavo (Cirugía del Uruguay, 2019)
Fifty months ago, he was embarking on his final flight, recalling John B. Murphy. He was the petrel of national surgery. A man of unusual characteristics for this historical period of our profession and our culture, he was born in Montevideo, the son of a distinguished pediatrician and syndicalist, Dr. José Alberto Praderi and Mrs. Amalia González ....